TWallet ARM TrustZone Enabled Trustable Mobile Wallet: A Case for Cryptocurrency Wallets - Gameiro, Rafael Rodrigues (2022)
With the increasing popularity of Blockchains supporting virtual cryptocurrencies it has become more important to have secure devices supporting operations in trustable cryp- tocurrency wallets. These wallets, currently implemented as mobile Apps or components of mobile Apps must be protected from possible intrusion attacks. ARM TrustZone technology has made available an extension of the ARM processor ar- chitecture, allowing for the isolation of trusted and non-trusted execution environments. Critical components and their runtime support can be "booted" and loaded to run in the isolated execution environment, backed by the ARM processor. The ARM TrustZone solution provides the possible enforcement of security and privacy conditions for applica- tions, ensuring the containment of sensitive software components and data-management facilities, isolating them from OS-level intrusion attacks. The idea is that sensitive compo- nents and managed data are executed with a trust computing base supported at hardware and firmware levels, not affected by intrusions against non-protected OS-level runtime components. In this dissertation we propose TWallet: a solution designed as a generic model to sup- port secure and trustable Mobile Client Wallets (implemented as mobile Apps), backed by the ARM TrustZone technology. The objective is to manage local sensitive stored data and processing components in a trust execution environment isolated from the Android OS. We believe that the proposed TWallet framework model can also inspire other specific solutions that can benefit from the isolation of sensitive components in mobile Android Apps. As a proof-of-concept, we used the TWallet framework model to implement a trusted wallet application used as an Ethereum wallet, to operate with the Ethereum Blockchain. To achieve our goals, we also conducted different experimental observations to analyze and validate the solution, with the implemented wallet integrated, tested and validated with the Rinkeby Ethereum Test Network.